BUILDING BETTER LEARNERS: A REVIEW OF KINDNESS-CENTERED APPROACHES IN ENGLISH LANGUAGE TEACHING - Suci Tresna Dewi Handayani; Titania Sari; Rimba Krisnha Sukma Dewi; Multi Nadeak (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT This article analyzes the implementation of kindness oriented instructional approaches in English Language Teaching (ELT). English learning generally still emphasizes mastery of linguistic competencies, such as grammar, vocabulary, and academic achievement, while important aspects of character development, empathy, and social skills tend to receive less attention. This study uses a qualitative literature review method by carefully examining journal articles and other academic sources relevant to kindness-based pedagogy in the context of ELT and education. The literature review is supplemented with academic reflections involving four lecturers from different scholarly backgrounds, namely two lecturers in English pedagogy and two lecturers with expertise in moral education and positive values. The literature analysis results show that kindness-oriented instructional approaches, such as Social Emotional Learning (SEL), Loving Pedagogy, and Altruistic Teaching, significantly contribute to creating an inclusive and supportive learning environment. These approaches are related to improving language competence, emotional well-being, classroom interaction, as well as students’ interpersonal communication skills and collaborative learning abilities. The study concludes that the integration of kindness-oriented pedagogical approaches in ELT strongly supports academic achievement as well as holistic student development. The contribution of this article is providing a comprehensive conceptual review of kindness-based ELT that can serve as an alternative in effectively integrating character education into language learning. ABSTRAK Artikel ini menganalisis penerapan pendekatan pembelajaran berorientasi kebaikan (kindness oriented instructional approaches) dalam pembelajaran Bahasa Inggris (English Language Teaching/ELT). Pembelajaran Bahasa Inggris pada umumnya masih menitikberatkan pada penguasaan kompetensi linguistik, seperti tata bahasa, kosakata, dan pencapaian akademik, sementara aspek pengembangan karakter, empati, dan keterampilan sosial cenderung kurang mendapatkan perhatian. Penelitian ini menggunakan metode kajian pustaka kualitatif dengan menelaah artikel jurnal dan sumber akademik yang relevan dengan pedagogi berbasis kebaikan dalam konteks ELT dan pendidikan. Kajian pustaka ini dilengkapi dengan refleksi akademik yang melibatkan empat dosen dari latar belakang keilmuan berbeda, yaitu dua dosen bidang pedagogi Bahasa Inggris dan dua dosen yang memiliki keahlian dalam pendidikan moral dan nilai-nilai positif. Hasil analisis literatur menunjukkan bahwa pendekatan pembelajaran berorientasi kebaikan, seperti Social Emotional Learning (SEL), Loving Pedagogy, dan Altruistic Teaching, berkontribusi terhadap terciptanya lingkungan belajar yang inklusif dan suportif. Pendekatan tersebut berkaitan dengan peningkatan kompetensi bahasa, kesejahteraan emosional, interaksi kelas, serta keterampilan komunikasi interpersonal peserta didik. Simpulan penelitian ini menegaskan bahwa integrasi pendekatan pedagogis berorientasi kebaikan dalam ELT mendukung pencapaian akademik sekaligus pengembangan peserta didik secara holistik. Kontribusi artikel ini adalah penyediaan tinjauan konseptual mengenai pembelajaran ELT berbasis kebaikan yang dapat menjadi alternatif dalam mengintegrasikan pendidikan karakter ke dalam pembelajaran bahasa.